Verb to be in Progressive Tense in American English - Wiangin, Nanthanut; Sukkrong, Jiraporn; Kaewkamjan, Kanaporn; Phonkamjad, Wanwipang; Promchitta, Viyada; Phanon, Wichien (วารสารพุทธปรัชญาวิวัฒน์, 2022)
The purposes of this study were to threefold as follows: 1) to determine whether “be” is auxiliary verb in progressive or not in (1) He’s studying in his room and (2) He’s in his room studying. 2) To investigate whether “be” is finite or non-finite verb in progressive tense of American English in (1) He’s studying in his room and (2) He’s in his room studying. 3) To investigate whether “studying” is complement or present participle. The instrument used in this study was the grammar checklist designed by the researchers from extensive analysis of related literatures and consultation with experts. The researchers obtained the data by inquiring the seven American native speakers and analyzed the data by syntactic approach. This study met that “be” is auxiliary verb in progressive tense when American native speakers focuses on location. Then it could prove that “studying” is present participle in progressive tense; nevertheless, adverb of place was situated following “be”.